Digital Skills in Higher Education: A Necessity of Civil Engineers’ Training (Docentes 2.0 Journal, 2022)
The global pandemic of COVID-19 reached Chiapas in March 2020; with it, the educational development of students was complicated due to the low accessibility of technology that persists in the State. The present objective was to determine the standard of digital skills that responds to the training needs of indigenous students upon admission to the degree in Civil Engineering (CI) of UNACH. This work was carried out under the humanistic paradigm, qualitative approach, documentary research, topic design, descriptive type with documentary analysis technique, which allowed us to search, organize and analyze documents published by international and national organizations, such as addition, the review of the State of the art to know the standards that can be selected for the evaluation of said skills. The content of texts at their semantic level was analyzed, and the study of the categories and dimensions of the investigation of seven standards that regulate the development of said skills was also carried out. In the present research, it can be concluded that the project entitled "Digital Skills Matrix" of the Department of Computing and Information and Communication Technologies (DGTIC) of the UNAM responds to training the student of the upper-middle-class level or level superior to indigenous origin. It is, without a doubt, an opportunity to help students in their academic career at IC to provide them with more and better tools for their future professional success.
Keywords: Digital skills; higher education